Perspektif Hukum Islam dan Hukum Positif Tentang Batas Usia Perkawinan - Sakinah Azzahra Hsb; Nursania Dasopang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the perspectives of Islamic law and positive law regarding the age limit for marriage. Age is generally seen as an indicator of maturity, though it is not always a reliable measure. The aim of this study is to explore the views of both Islamic law and positive law on the marriage age limit and its relevance in today's context. The research employs a normative juridical method, focusing on the applicable legal regulations. The findings reveal that Islamic law does not specify a particular age limit for marriage; rather, it relates to the stages of baligh (maturity) and rushd (wisdom). In contrast, positive law sets the marriage age limit for both men and women at 19 years.